2019
DOI: 10.1111/jopr.13119
|View full text |Cite
|
Sign up to set email alerts
|

Technical Complications and Prosthesis Survival Rates with Implant‐Supported Fixed Complete Dental Prostheses: A Retrospective Study with 1‐ to 12‐Year Follow‐Up

Abstract: Purpose:To report the rate of technical complications and prosthesis survival in a cohort of edentulous patients treated with implant-supported fixed complete dental prostheses (IFCDPs) after a mean observation period of at least 1 year. Materials and Methods: The single-visit examination included clinical and radiographic assessment, occlusal analysis, photographs and questionnaire assessing patient satisfaction in a cohort of 52 patients rehabilitated with 71 IFCDPs (supported by 457 implants). The IFCDPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 28 publications
7
76
2
Order By: Relevance
“…Compared with acceptable survival rate, the complication-free survival rate was relatively low with only 26.0% of patients and 37.0% of implants showing no complication over 10 years. The result was in line with a previous retrospective study including 71 implant-supported fixed complete dental prostheses (Papaspyridakos et al, 2020). The complication-free survival at 10-year was 30.1%…”
Section: Discussionsupporting
confidence: 91%
“…Compared with acceptable survival rate, the complication-free survival rate was relatively low with only 26.0% of patients and 37.0% of implants showing no complication over 10 years. The result was in line with a previous retrospective study including 71 implant-supported fixed complete dental prostheses (Papaspyridakos et al, 2020). The complication-free survival at 10-year was 30.1%…”
Section: Discussionsupporting
confidence: 91%
“…However, the meta‐analysis pooled data from both partially and completely edentulous patients. 15 With the percentage of older patients as well as the incidence of edentulous patients rising, coupled with the increase of life expectancy, the need of fixed implant rehabilitation for the growing edentulous population is constantly increasing 24‐26 . Additionally, there is a demand to simplify the fixed implant rehabilitation protocol, to reduce biologic and technical complications and morbidity, and to shorten treatment time for this population 27‐30 .…”
mentioning
confidence: 99%
“…Previous studies have revealed that technical complications occasionally occur, although at low incidences [41,42]. The incidences of wear and fracture are 19.4% and 0.7%, respectively, for titanium frameworks and 7.3% and 5.9% for zirconia [43]. In consideration of possible changes in roughness due to chipping, further analysis, including the incidence of chipping, is needed.…”
Section: Discussionmentioning
confidence: 99%